Three-dimensional solution structure and conformational plasticity of the N-terminal scavenger receptor cysteine-rich domain of human CD5. - Garza-Garcia, A; Esposito, D; Rieping, W; Harris, R; Briggs, C; Brown, M; Driscoll, P (2008)
The lymphocyte receptor CD5 influences cell activation by modifying the strength of the intracellular response initiated by antigen engagement. Regulation through CD5 involves the interaction of one or more of its three scavenger receptor cysteine-rich domains present in the extracellular region. Here, we present the 3D solution structure of a non-glycosylated double mutant of the N-terminal domain of human CD5 expressed in Escherichia coli (eCD5d1m), which has enhanced solubility compared to the non-glycosylated wild-type (eCD5d1). In common with a glycosylated form expressed in Pichia pastoris, the [(15)N,(1)H]-correlation spectra of both eCD5d1 and eCD5d1m exhibit non-uniform temperature-dependent signal intensities, indicating extensive conformational fluctuations on the micro-millisecond timescale. Although approximately one half of the signals expected for the domain are absent at 298 K, essentially complete resonance assignments and a solution structure could be obtained at 318 K. Because of the sparse nature of the experimental restraint data and the potentially important contribution of conformational exchange to the nuclear Overhauser effect peak intensity, we applied inferential structure determination to calculate the eCD5d1m structure. The inferential structure determination ensemble has similar features to that obtained by traditional simulated annealing methods, but displays superior definition and structural quality. The eCD5d1m structure is similar to other members of the scavenger receptor cysteine-rich superfamily, but the position of the lone alpha helix differs due to interactions with the unique N-terminal region of the domain. The availability of an experimentally tractable form of CD5d1, together with its 3D structure, provides new tools for further investigation of its function within intact CD5.